2004
DOI: 10.1038/ncb1092
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage checkpoint and PKA pathways converge on APC substrates and Cdc20 to regulate mitotic progression

Abstract: The conserved checkpoint kinases Chk1 and Rad53-Dun1 block the metaphase to anaphase transition by the phosphorylation and stabilization of securin, and block the mitotic exit network regulated by the Bfa1-Bub2 complex. However, both chk1 and rad53 mutants are able to exit from mitosis and initiate a new cell cycle, suggesting that both pathways have supporting functions in restraining anaphase and in blocking the inactivation of mitotic cyclin-Cdk1 complexes. Here we find that the cyclic-AMP-dependent protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 34 publications
4
106
0
1
Order By: Relevance
“…Therefore, complementation by other mitotic cyclins was less efficient when G 2 /M checkpoint was activated. This could possibly be due to deregulated activity of the anaphase-promoting complex/cyclosome-Cdc20 that is regulated by mitotic cyclins 6,48,49 but also by DNA damage checkpoint [50][51][52][53][54][55] and reciprocally controls the stability/turnover of mitotic cyclins. 56 Interestingly, a role for Cdc20 in controlling spindle length and the stability of kinetochore microtubule in response to genotoxic stress has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, complementation by other mitotic cyclins was less efficient when G 2 /M checkpoint was activated. This could possibly be due to deregulated activity of the anaphase-promoting complex/cyclosome-Cdc20 that is regulated by mitotic cyclins 6,48,49 but also by DNA damage checkpoint [50][51][52][53][54][55] and reciprocally controls the stability/turnover of mitotic cyclins. 56 Interestingly, a role for Cdc20 in controlling spindle length and the stability of kinetochore microtubule in response to genotoxic stress has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the checkpoint proteins in addition to the kinase Chk1 and the mediator/signal amplifier protein Rad9 inhibit spindle elongation and chromosome segregation in response to DNA damage sensed in late S or G 2 . One effector of Chk1 in this response is the securin Pds1, which is stabilized by phosphorylation in response to DNA damage (3)(4)(5)(6). Although the Chk1/Rad9 DNA damage checkpoint arm is not required during replication blocks in the budding yeast, we have shown that Chk1 is activated when replication is slowed down by the ribonucleotide reductase inhibitor hydroxyurea (HU).…”
mentioning
confidence: 92%
“…In yeast, Cdc5 phosphorylates and activates the Anaphase Promoting Complex (APC). The P. falciparum kinase found to be closest sequence-wise to higher eukaryotic Polo kinases is PfPKA, and yeast/mammalian PKA is also known to phosphorylate APC with the opposite effect of suppressing its activity [92]. Therefore, Polo kinases and PKA regulate mitotic progression by controlling APC activity in opposing ways.…”
Section: The Cmgc Group and Other Cell Cycle Control Kinasesmentioning
confidence: 99%